Alkali residue-based flow state solidified soil and manufacturing method thereof
By combining solid waste such as fly ash, blast furnace slag, etc. into alkali slag-based fluid solidified soil, and adding appropriate amounts of hydrating agents and admixtures, the problem of low strength of alkali slag in building materials is solved, and a high-strength skeleton structure and full cementation are achieved, meeting the needs of engineering construction.
Patent Information
- Application Number
- CN202411624773.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-28
AI Technical Summary
The large amount of alkali slag used in building materials will lead to low material strength and it is difficult to meet the needs of engineering construction.
By combining solid waste such as fly ash, blast furnace slag, vanadium tailings, aluminum slag and other solid waste with alkali slag, and adding an appropriate amount of hydrating agent and admixture to the alkali slag-based fluid solidified soil, a high-strength framework structure is formed to achieve sufficient cementation of each component.
It effectively fills pores and cracks in the fluidized solidified soil of alkali slag-based fluid, overcomes the defects of loose alkali slag structure, significantly improves the strength of the material, and can meet the needs of engineering construction.
Smart Images

Figure BDA0005134441010000101 
Figure BDA0005134441010000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of civil engineering materials, and more specifically, to an alkali slag-based fluidized solidified soil and a manufacturing method thereof. Background Art
[0002] Alkali residue is the waste residue produced in the process of making soda ash by the ammonia-soda process, which mainly comes from the process of distilling and recovering ammonia by the ammonia-soda process. According to the current technological level, 0.3-0.6 tons of alkaline residue will be produced for every ton of soda ash produced. According to statistics, most of my country's soda ash production enterprises adopt the ammonia-soda process, accounting for about 60% of the total soda ash production. The annual discharge of alkaline residue is as high as 6-12 million tons, and this number is increasing year by year with the expansion of production capacity. At present, ammonia-soda plants generally use the method of slag yard stacking. The stacking of alkaline residue will occupy land, erode soil, destroy vegetation, pollute the environment, and require a lot of manpower, money and materials to manage. The alkaline residue problem has become a bottleneck problem restricting the survival and development of ammonia-soda enterprises.
[0003] Although the large amount of alkali residue piled up will cause serious waste of resources and environmental pollution, it does not mean that alkali residue has no benefits but only harms. The main components of alkali residue include calcium carbonate, calcium sulfate, chloride salt and other components. Although these components are difficult to separate and the cost of classification and extraction is high, if the alkali residue can be applied to the right occasion, it can generate certain economic value while disposing of the alkali residue, which is also in line with the concept of sustainable development and green environmental protection. Based on this principle, there are precedents for applying alkali residue in construction projects.
[0004] With regard to the above-mentioned related technologies, the inventor believes that although the use of alkali slag in construction projects can achieve the disposal of alkali slag, the large-scale use of alkali slag will also have a negative impact on the overall mechanical properties of the material. Therefore, the strength of the building materials obtained according to this method is often low, which is difficult to fully meet the needs of engineering construction. Summary of the invention
[0005] In the related art, the large amount of alkali slag used will also have a negative impact on the overall mechanical properties of the material, resulting in the obtained building material often having low strength and being difficult to fully meet the needs of engineering construction. In order to improve this defect, the present application provides an alkali slag-based fluidized solidified soil and a manufacturing method thereof.
[0006] In the first aspect, the present application provides an alkali slag-based fluidized solidified soil, which adopts the following technical solution:
[0007] A kind of alkali slag-based fluidized solidified soil, the fluidized solidified soil comprises the following raw materials in parts by weight: 10-15 parts of cement, 75-95 parts of alkali slag, 8-10 parts of fly ash, 20-30 parts of blast furnace slag, 14-23 parts of silicoaluminate auxiliary materials, 2.8-7.6 parts of admixtures; the admixtures comprise early strength agent, sodium citrate, warm wheel glue, and water reducer; the water reducer comprises polycarboxylate water reducer, and the silicoaluminate auxiliary materials comprise vanadium tailings and aluminum slag.
[0008] By adopting the above technical scheme, the present application selects fly ash, blast furnace slag, vanadium tailings, aluminum slag and other solid wastes and compound them with alkali slag to achieve full utilization of industrial solid waste (wherein, vanadium tailings refer to tailings produced by acid leaching of vanadium from vanadium ore, the main component of which is silicon dioxide, and aluminum slag refers to alumina-based catalyst waste, the main component of which is aluminum oxide). The calcium hydroxide in the alkali slag and the calcium hydroxide produced by cement hydration can react with the above solid wastes to convert active silicon dioxide into hydrated calcium silicate and active aluminum oxide into hydrated calcium aluminate. The reaction principle can be expressed as: Ca(OH)2+SiO2+(n-1)H2O→CaO·SiO2·nH2O; Ca(OH)2+Al2O3+(n-1)H2O→CaO·Al2O3·nH2O. The hydrated calcium silicate and hydrated calcium aluminate formed by the above reaction are both in a gel state and can fill the pores and cracks inside the solidified soil. The combination of fly ash and blast furnace slag can transform the alkali slag from a flocculent structure to a skeleton structure in the microstructure, which is beneficial to the increase of strength. The vanadium tailings and aluminum slag can supplement active silicon dioxide and active aluminum oxide respectively, thereby promoting the formation of calcium silicate hydrate and calcium aluminate hydrate. Both the alkali slag and the vanadium tailings contain a certain amount of gypsum, and gypsum can react with calcium silicate hydrate and calcium aluminate hydrate to produce calcium sulphoaluminate hydrate. Calcium silicate hydrate, calcium aluminate hydrate, and calcium sulphoaluminate hydrate are all hydraulic compounds, which have a good cementing effect on the loose particles in the alkali slag. The large amount of chloride ions contained in the alkali slag can also react with calcium aluminate hydrate to produce high-strength calcium chloroaluminate hydrate, thereby further achieving reinforcement. In addition, the present application also selects a warm wheel glue with good alkali resistance, and uses sodium citrate and polycarboxylic acid water reducer to jointly adjust the fluidity, which is conducive to the full development of the strength of the fluidized solidified soil. Under the synergistic effect of the above-mentioned components, the pores and cracks in the alkali slag-based fluidized solidified soil of the present application can be effectively filled, and the defect of the loose structure of the alkali slag itself is overcome, forming a high-strength skeleton structure and achieving sufficient bonding of the various components, so that the material as a whole can have a higher strength and can fully meet the needs of engineering construction.
[0009] Preferably, the alumina content of the blast furnace slag is 14-20%.
[0010] By adopting the above technical scheme, the present application optimizes the alumina content of blast furnace slag, which helps to increase the production of calcium aluminate hydrate, thereby promoting the production of calcium chloroaluminate hydrate and calcium sulphoaluminate hydrate, and improving the strength of fluidized solidified soil.
[0011] Preferably, the fluidized solidified soil further comprises recycled solid waste powder, and the recycled solid waste powder is prepared according to the following method:
[0012] (1) crushing the solid waste, grinding it, and then sieving it to obtain a primary ground powder; in this step, the solid waste used includes lithium slag;
[0013] (2) Dry the primary ground powder to constant weight, then calcine it at 700-900°C, wait for it to cool down, grind it again, and obtain the recycled solid waste powder after screening.
[0014] By adopting the above technical scheme, the present application uses lithium slag as a representative of solid waste raw materials, activates it by high-temperature calcination, and obtains regenerated solid waste powder. The kaolin component in the lithium slag removes hydroxyl groups during the calcination process, and the crystal surface structure is destroyed to form amorphous silicon dioxide and aluminum oxide, which has a good promoting effect on cement hydration, and can also increase the total amount of hydrated calcium silicate and hydrated calcium aluminate, which helps to fully improve the strength of fluidized solidified soil.
[0015] Preferably, the average particle size of the recycled solid waste powder is 20-40 μm.
[0016] By adopting the above technical solution, the present application optimizes the particle size range of the recycled solid waste powder, which helps to improve the strength of the fluidized solidified soil.
[0017] Preferably, the components of the regenerated solid waste powder also include bauxite tailings.
[0018] By adopting the above technical solution, the bauxite tailings activated at high temperature have good volcanic ash activity, which can increase the consumption of calcium hydroxide and produce more CSH gel products. The increase of gel products makes the internal structure of the fluidized solidified soil more compact, improves the bonding effect between the components, and helps to improve the strength of the fluidized solidified soil.
[0019] Preferably, in the method for preparing the regenerated solid waste powder, a combustion aid is mixed with the primary ground powder and then calcined together, and the combustion aid includes one of dehydrated rice husk and highland barley straw powder.
[0020] By adopting the above technical solution, both dehydrated rice husk and highland barley straw powder can be used as combustion aids, which helps to evenly heat the solid waste powder. At the same time, the ash produced after the dehydrated rice husk and highland barley straw powder are burned can also participate in the formation of C-(A)-SH gel, increase the density of the fluidized solidified soil, and help improve the strength performance of the fluidized solidified soil.
[0021] Preferably, the fluidized solidified soil also includes basalt fibers.
[0022] By adopting the above technical solution, basalt fiber can be used as a reinforcing phase of fluidized solidified soil. When cracking is caused by external force, the high elastic modulus of basalt fiber can delay and limit the development of cracks. In addition, the fluidized solidified soil of the present application can form a relatively dense structure, so the addition of basalt fiber can further improve the strength of the fluidized solidified soil.
[0023] Preferably, the admixture further comprises sulfonated lignin, and the sulfonated lignin is prepared according to the following method:
[0024] Deionized water, lignin and ferric chloride are mixed, and then the pH value is adjusted, and a sodium sulfite solution is added under heating conditions in a water bath, and the heating reaction is continued to obtain sulfonated lignin.
[0025] By adopting the above technical solution, the present application sulfonates lignin to obtain sulfonated lignin, and uses the sulfonated lignin as an admixture. The addition of sulfonated lignin further promotes the dispersion and hydration reaction of components such as cement and slag, thereby improving the strength performance of fluidized solidified soil.
[0026] Preferably, the amount of ferric chloride used is 0.15-0.25% of the weight of lignin.
[0027] By adopting the above technical solution, the present application optimizes the dosage range of ferric chloride, which helps to fully realize the sulfonation of lignin, enhances the anti-clay performance of sulfonated lignin, and helps to improve the strength of fluidized solidified soil.
[0028] In a second aspect, the present application provides a method for manufacturing alkali slag-based fluidized solidified soil, which adopts the following technical solution.
[0029] A method for manufacturing alkali slag-based fluidized solidified soil comprises the following steps:
[0030] (1) Mixing the solid components except the additive to obtain a dry mix, which is set aside; mixing the additive and water to obtain an additive solution, which is set aside;
[0031] (2) The admixture solution and the dry mixed material are mixed and stirred to obtain a mixture, and the mixture is put into a mold for curing to obtain an alkali slag-based fluidized solidified soil.
[0032] By adopting the above technical scheme, the present application first prepares the dry mix and the slurry separately, and then mixes the two to form a mixture. By putting the mixture into a mold for curing, the mixture is hardened to obtain alkali slag-based fluidized solidified soil.
[0033] In summary, this application has the following beneficial effects:
[0034] 1. This application uses fly ash, blast furnace slag, vanadium tailings, aluminum slag and other solid wastes to compound with alkali slag. Under the synergistic effect of the above components, the pores and cracks in the alkali slag-based fluidized solidified soil can be effectively filled, and the defect of the loose structure of the alkali slag itself is overcome, forming a high-strength skeleton structure, achieving full bonding of the components, so that the material as a whole can have a higher strength and can fully meet the needs of engineering construction.
[0035] 2. The present application activates lithium slag and bauxite tailings by high-temperature calcination to obtain regenerated solid waste powder. After calcination, lithium slag forms amorphous silicon dioxide and aluminum oxide, which have a good promoting effect on cement hydration, and can also increase the total amount of hydrated calcium silicate and hydrated calcium aluminate, which helps to fully improve the strength of fluidized solidified soil; and the bauxite tailings activated by high temperature have good volcanic ash activity, which can increase the consumption of calcium hydroxide and produce more CSH gel products. The increase in CSH gel products makes the internal structure of the fluidized solidified soil more compact, and improves the bonding effect between the components, which also helps to improve the strength of the fluidized solidified soil.
[0036] 3. This application also uses dehydrated rice husk and highland barley straw powder as combustion aids. In addition to their combustion-supporting effects, the ash produced by combustion can also participate in the formation of C-(A)-SH gel, thereby increasing the density of the fluidized solidified soil and thus improving the strength properties of the fluidized solidified soil. DETAILED DESCRIPTION
[0037] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0038] Preparation example of recycled solid waste powder
[0039] The following is an explanation using Preparation Example 1.
[0040] Preparation Example 1
[0041] In this preparation example, the solid waste used includes lithium slag, and the silicon dioxide content of the lithium slag is 78.84wt%, the aluminum oxide content is 8.12wt%, the calcium sulfate content is 4.15wt%, the total content of sodium oxide and potassium oxide is 4.73wt%, and the remainder is impurities.
[0042] In this preparation example, the recycled solid waste powder is prepared according to the following method:
[0043] (1) crushing the solid waste, grinding it, and then passing it through a 3 mm sieve to obtain primary ground powder;
[0044] (2) Dry the primary ground powder at 105°C to constant weight, then heat it to 700°C (referred to as calcination temperature) at a rate of 5°C / min, keep it at that temperature for 1 h, then stop heating, wait for the product to cool to 25°C, and grind it again. After screening, a recycled solid waste powder with an average particle size of 50 μm is obtained.
[0045] Preparation Example 2
[0046] This Preparation Example is different from Preparation Example 1 in that the calcination temperature is adjusted from 700°C to 800°C.
[0047] Preparation Example 3
[0048] This Preparation Example is different from Preparation Example 1 in that the calcination temperature is adjusted from 700°C to 900°C.
[0049] Preparation Example 4
[0050] The difference between this preparation example and preparation example 3 is that the average particle size of the recycled solid waste powder is 40 μm.
[0051] Preparation Example 5
[0052] The difference between this preparation example and preparation example 3 is that the average particle size of the recycled solid waste powder is 30 μm.
[0053] Preparation Example 6
[0054] The difference between this preparation example and preparation example 3 is that the average particle size of the recycled solid waste powder is 20 μm.
[0055] Preparation Example 7
[0056] The difference between this preparation example and preparation example 6 is that the regenerated solid waste powder is composed of lithium slag and bauxite tailings in a weight ratio of 1:1, and the oxide composition of the bauxite tailings is: silicon dioxide 36.45wt%, aluminum oxide 40.25wt%, iron oxide 10.26wt%, calcium oxide 2.94wt%, potassium oxide 3.44wt%, titanium dioxide 3.21wt%, sulfur trioxide 1.73wt%, magnesium oxide 0.56wt%, and the remainder is impurities.
[0057] Preparation Example 8
[0058] The difference between this preparation example and preparation example 7 is that in the method for preparing the recycled solid waste powder, the combustion aid and the primary ground powder are mixed in a weight ratio of 1:1 and then calcined together, and the combustion aid is dehydrated rice husk, and the combustion weight loss rate of the dehydrated rice husk is 90.4%. The oxide composition of the ash obtained by burning the dehydrated rice husk is as follows: 0.6wt% calcium oxide, 89.8wt% silicon dioxide, 0.4wt% aluminum oxide, and the remainder is impurities.
[0059] Preparation Example 9
[0060] The difference between this preparation example and preparation example 8 is that the combustion aid is highland barley straw powder, which is dried to constant weight at 105°C in advance, and the combustion weight loss rate of highland barley straw powder is 92.1%. The oxide composition of the ash obtained by burning highland barley straw powder is as follows: 61.24wt% silicon dioxide, 10.45wt% calcium oxide, 5.98wt% aluminum oxide, 1.66wt% sulfur trioxide, 2.01wt% magnesium oxide, 3.91wt% iron oxide, 5.16wt% potassium oxide, 2.35wt% sodium oxide, 5.54wt% phosphorus pentoxide, and the remainder is impurities.
[0061] Preparation example of sulfonated lignin
[0062] The following is an explanation using Preparation Example 10 as an example.
[0063] Preparation Example 10
[0064] In this preparation example, sulfonated lignin was prepared according to the following method:
[0065] Deionized water, lignin and ferric chloride were mixed in a weight ratio of 150 mL: 10 g: 0.015 g, and then the pH value was adjusted to 12. Sodium sulfite was added under heating conditions at 80° C. in a water bath (the amount of sodium sulfite was 40% of the weight of lignin), and the heating reaction was continued for 5 hours to obtain sulfonated lignin.
[0066] Example
[0067] Examples 1-5
[0068] The following description is given by taking Example 1 as an example.
[0069] Example 1
[0070] The present embodiment provides an alkali slag-based fluidized solidified soil. The raw materials for preparing the fluidized solidified soil include the following components: 10 kg of cement, 75 kg of alkali slag, 8 kg of fly ash, 20 kg of blast furnace slag, 14 kg of siliceous and aluminous auxiliary materials (including 10 kg of vanadium tailings and 4 kg of aluminum slag), 2.8 kg of admixtures (including 0.5 kg of early strength agent, 0.7 kg of sodium citrate, 0.5 kg of warm wheel glue, and 1.1 kg of water reducer, and the water reducer is a polycarboxylic acid water reducer).
[0071] In this embodiment, the cement is P.O42.5 silicate cement; the liquid limit of the alkali slag is 62.5%, the plastic limit is 47.8%, the plasticity index is 13.5, the particle size is mainly concentrated in the powder particle area (0.075mm-0.005mm), and the powder particles account for about 88.2% of the total particles of the alkali slag; the chemical composition of the alkali slag is: calcium carbonate 59%, calcium hydroxide 12%, calcium chloride 8%, sodium chloride 5%, calcium sulfate 5%, silicon dioxide 4%, aluminum oxide 3%, and the rest are impurities. The fly ash is F class I fly ash; the specific surface area of blast furnace slag is 458m 2 / kg, alumina content is 10%; the average particle size of vanadium tailings is 8.5μm, silica content is 74.85%, gypsum content is 11.26%; the average particle size of aluminum slag is 10.6μm, alumina content is 70.48%. Ferric chloride is used as early strength agent, and the water reduction rate of polycarboxylate water reducer is 28%.
[0072] This embodiment provides a method for manufacturing alkali slag-based fluidized solidified soil, comprising the following steps:
[0073] (1) Mixing the solid components except the additive to obtain a dry mix, which is set aside; mixing the additive and water to obtain an additive solution, which is set aside;
[0074] (2) The admixture solution and the dry mixed material are mixed and stirred to obtain a mixture, and the mixture is put into a mold for curing to obtain an alkali slag-based fluidized solidified soil.
[0075] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the fluidized solidified soil.
[0076] Table 1 Raw material ratio of fluidized solidified soil
[0077]
[0078] Example 6
[0079] The difference between this embodiment and embodiment 5 is that the alumina content of the blast furnace slag is 14%.
[0080] Example 7
[0081] The difference between this embodiment and embodiment 5 is that the alumina content of the blast furnace slag is 17%.
[0082] Example 8
[0083] The difference between this embodiment and embodiment 5 is that the alumina content of the blast furnace slag is 20%.
[0084] Example 9
[0085] The difference between this embodiment and embodiment 8 is that the components of the fluidized solidified soil also include 10 kg of recycled solid waste powder, and the recycled solid waste powder is prepared according to the method of preparation example 1.
[0086] As shown in Table 2, the difference between Examples 9-17 is that the preparation examples of the recycled solid waste powder are different.
[0087] Table 2 Preparation example of recycled solid waste powder
[0088] sample Preparation Example Example 9 Preparation Example 1 Example 10 Preparation Example 2 Embodiment 11 Preparation Example 3 Example 12 Preparation Example 4 Example 13 Preparation Example 5 Embodiment 14 Preparation Example 6 Embodiment 15 Preparation Example 7 Example 16 Preparation Example 8 Embodiment 17 Preparation Example 9
[0089] Embodiment 18
[0090] The difference between this embodiment and Embodiment 17 is that the components of the fluidized solidified soil also include basalt fiber, the amount of basalt fiber used is 5% of the weight of the alkali slag, and the basalt fiber is mixed with silt soil, silt sand, sand and gravel in the step (1) of preparing the alkali slag-based fluidized solidified soil.
[0091] Embodiment 19
[0092] The difference between this embodiment and embodiment 18 is that the admixture further includes 3.5 kg of sulfonated lignin, and the sulfonated lignin is prepared according to the method of preparation example 10.
[0093] Comparative Example
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that the raw material components of the fluidized solidified soil do not include vanadium tailings and aluminum slag.
[0096] Comparative Example 2
[0097] The difference between this comparative example and Example 1 is that the raw material components of the fluidized solidified soil do not include vanadium tailings.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the raw material components of the fluidized solidified soil do not include aluminum slag.
[0100] Comparative Example 4
[0101] The difference between this comparative example and Example 1 is that the fly ash is replaced with blast furnace slag of the same weight.
[0102] Comparative Example 5
[0103] The difference between this comparative example and Example 1 is that the blast furnace slag is replaced by the same weight of fly ash.
[0104] Performance testing methods
[0105] Sample preparation:
[0106] The specimens were prepared according to the cylindrical specimen preparation method described in the specification "Test Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009). After demolding, the specimens were placed in a ventilated and dry place indoors for natural curing (temperature of 25°C ± 2°C, humidity of 70% ± 5%). The curing age was 28 days and the compaction degree was 95%.
[0107] Test plan:
[0108] Unconfined compressive strength test: According to the requirements of the Highway Geotechnical Test Code (JTG 3430-2020), a strain-controlled unconfined compressive strength instrument was used for testing. After the test, the compressive strength of Comparative Example 1 was used as a benchmark to calculate the ratio between the compressive strength of each embodiment and the comparative example and the compressive strength of Comparative Example 1, and the ratio was recorded as the relative compressive strength. The results are shown in Table 3.
[0109] Table 3 Relative compressive strength
[0110]
[0111] It can be seen from Examples 1-5 and Comparative Example 1 and Table 3 that the relative compressive strengths measured in Examples 1-5 are all higher than those in Comparative Example 1. This is because the present application utilizes the synergistic effect of components such as fly ash, blast furnace slag, vanadium tailings, aluminum slag, and alkali slag, so that the pores and cracks in the alkali slag-based fluidized solidified soil can be effectively filled, and the defect of the loose structure of the alkali slag itself is overcome, a high-strength skeleton structure is formed, and sufficient bonding of the components is achieved, so that the material as a whole can have a higher strength and can fully meet the needs of engineering construction.
[0112] Combining Example 1 and Comparative Example 2 and Table 3, it can be seen that the relative compressive strength measured in Example 1 is higher than that in Comparative Example 1. This is because in the absence of vanadium tailings, the active silica and calcium sulfate contents in Comparative Example 2 are relatively low, which affects the production of calcium silicate hydrate and calcium sulfoaluminate hydrate, resulting in a decrease in strength performance.
[0113] Combining Example 1 and Comparative Example 3 and Table 3, it can be seen that the relative compressive strength measured in Example 1 is higher than that in Comparative Example 2. This is because in the absence of aluminum slag, the active alumina in Comparative Example 3 is less, which affects the production of calcium aluminate hydrate and calcium sulfoaluminate hydrate, resulting in a decrease in strength performance.
[0114] Combining Example 1 and Comparative Examples 4-5 and Table 3, it can be seen that the relative compressive strength measured in Comparative Examples 4-5 is relatively low. This is because Comparative Examples 4-5 do not achieve the combination of fly ash and blast furnace slag, resulting in the alkali slag failing to fully transform from a flocculant structure to a skeleton structure in terms of the microstructure, resulting in a decrease in strength performance.
[0115] Combining Example 3 with Examples 6-8 and Table 3, it can be seen that the relative compressive strength measured in Examples 6-8 is relatively high. This is because when the alumina content of the blast furnace slag is 14-20%, more calcium aluminate hydrate can be produced in the fluidized solidified soil, and at the same time, it also indirectly promotes the formation of calcium chloroaluminate hydrate, thereby improving the strength performance of the fluidized solidified soil.
[0116] Combining Example 8, Examples 9-14 and Table 3, it can be seen that the relative compressive strength measured in Examples 9-14 is relatively high, indicating that the addition of recycled solid waste powder helps to improve the strength performance of fluidized solidified soil. Among them, the results of Examples 9-11 show that the recycled solid waste powder prepared in the range of 700-900°C has a significant improvement in strength, and the effect at 900°C is the best. Examples 12-14 show that the recycled solid waste powder with an average particle size of 20-40μm has a significant improvement in strength.
[0117] Combining Example 14, Example 15 and Table 3, it can be seen that the relative compressive strength measured in Example 15 is relatively high. This is because the bauxite tailings activated at high temperature have good volcanic ash activity, which can increase the consumption of calcium hydroxide and produce more CSH gel products. The increase in gel products makes the internal structure of the fluidized solidified soil more compact, improves the bonding effect between the components, and helps to improve the strength of the fluidized solidified soil.
[0118] It can be seen from Example 15, Examples 16-17 and Table 3 that the relative compressive strengths measured in Examples 16-17 are relatively high. On the one hand, this is because both the dehydrated rice husk and the highland barley straw powder can be used as combustion aids, which helps to evenly heat the solid waste powder. On the other hand, the ash produced after the combustion of the dehydrated rice husk and the highland barley straw powder can also participate in the formation of C-(A)-SH gel, thereby increasing the density of the fluidized solidified soil and helping to improve the strength properties of the fluidized solidified soil.
[0119] Combining Example 17 and Example 18 with Table 3, it can be seen that the relative compressive strength measured in Example 18 is relatively high, which is because the basalt fiber can be used as a reinforcing phase of the fluidized solidified soil. When cracking occurs due to external force, the high elastic modulus of the basalt fiber can delay and limit the cracks, and the fluidized solidified soil of the present application can form a relatively dense structure, so the addition of basalt fiber helps to fully improve the strength of the fluidized solidified soil.
[0120] It can be seen from Example 18 and Example 19 and Table 3 that the relative compressive strength measured in Example 19 is relatively high. This is because within this range, the addition of sulfonated lignin further promotes the dispersion and hydration reaction of components such as cement and slag, thereby improving the strength properties of the fluidized solidified soil.
[0121] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. An alkali slag-based fluidized solidified soil, characterized in that: The fluidized solidified soil comprises the following raw materials in parts by weight: 10-15 parts of cement, 75-95 parts of alkali slag, 8-10 parts of fly ash, 20-30 parts of blast furnace slag, 14-23 parts of silicoaluminous auxiliary materials, and 2.8-7.6 parts of admixtures; the admixtures comprise early strength agent, sodium citrate, warm wheel glue, and water reducer; the water reducer comprises polycarboxylate water reducer, and the silicoaluminous auxiliary materials comprise vanadium tailings and aluminum slag.
2. The alkali slag-based fluidized solidified soil according to claim 1, characterized in that: The alumina content of the blast furnace slag is 14-20%.
3. The alkali slag-based fluidized solidified soil according to claim 1, characterized in that: The components of the fluidized solidified soil also include recycled solid waste powder, and the recycled solid waste powder is prepared according to the following method: (1) crushing the solid waste, grinding it, and then sieving it to obtain a primary ground powder; in this step, the solid waste used includes lithium slag; (2) Dry the primary ground powder to constant weight, then calcine it at 700-900°C, wait for it to cool down, grind it again, and obtain the recycled solid waste powder after screening.
4. The alkali slag-based fluidized solidified soil according to claim 3, characterized in that: The average particle size of the recycled solid waste powder is 20-40 μm.
5. The alkali slag-based fluidized solidified soil according to claim 4, characterized in that: The components of the regenerated solid waste powder also include bauxite tailings.
6. The alkali slag-based fluidized solidified soil according to claim 4, characterized in that: In the method for preparing the regenerated solid waste powder, a combustion aid is mixed with the primary ground powder and then calcined together. The combustion aid includes one of dehydrated rice husk and highland barley straw powder.
7. The alkali slag-based fluidized solidified soil according to claim 6, characterized in that: The fluidized solidified soil also includes basalt fiber.
8. The alkali slag-based fluidized solidified soil according to claim 1, characterized in that: The admixture also includes sulfonated lignin, and the sulfonated lignin is prepared according to the following method: Deionized water, lignin and ferric chloride are mixed, and then the pH value is adjusted, and a sodium sulfite solution is added under heating conditions in a water bath, and the heating reaction is continued to obtain sulfonated lignin.
9. The alkali slag-based fluidized solidified soil according to claim 8, characterized in that: The amount of ferric chloride used is 0.15-0.25% of the weight of lignin.
10. The method for producing alkali slag-based fluidized solidified soil according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Mixing the solid components except the additive to obtain a dry mix, which is set aside; mixing the additive and water to obtain an additive solution, which is set aside; (2) The admixture solution and the dry mixed material are mixed and stirred to obtain a mixture, and the mixture is put into a mold for curing to obtain an alkali slag-based fluidized solidified soil.
Citation Information
Cited By
Homologous isomeric alkaline residue-based fluidized stabilized soil as well as preparation method and application of homologous isomeric alkaline residue-based fluidized stabilized soil
CN120943575A